The future of hospitality jobs: The rise of the gig worker - Georges El Hajal; Bill Rowson (Research in Hospitality Management, 2021)
This review article aims to analyse the different perspectives on the gig economy and gig workers, specifically in the hospitality industry, and establish a research base that contributes to future research. The article examines the perceptions of both employers and employees of the gig economy based on available literature. Current literature reveals that the impact of gig-style work is under-researched in many areas, including the hospitality sector. The COVID-19 pandemic and its restrictions have revitalised the gig economy and forced the hospitality industry to explore a sustainable long-term relationship with it. Many of today’s permanent hospitality jobs will be lost to gig workers. Governments and employers have to prepare and adapt to a future where the desire for flexibility is central. The article reviews the many advantages and disadvantages of the gig economy and offers an insight into the future of hospitality jobs. This review article is beneficial for both industrial and educational applications.